Relationship between Amniotic Fluid Index and Perinatal Outcome - Pradhan, S; Adhikary, A; Pradhan, P; Pradhan, S (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This study was done to evaluate the predictive value of low amniotic fluid index (AFI) of < 5 cm for adverse perinatal outcome in term of caesarean section for fetal distress, birth weight, meconium stained liquor and APGAR scores. Methods: This was a prospective study of 200 antenatal women booked at Nepal Medical College Teaching Hospital during the year 2013-2014 with gestational age between 34 and 41 weeks. Patients history and clinical examination were recorded and AFI was measured and the perinatal outcome was compared between two groups i.e AFI <5 cm and >5 cm. Results: The caesarean section (C/S) rate for fetal distress and low birth weight babies (<2.5 kg) was higher in patients with low AFI (p=0.048, 0.001 respectively). There was no significant difference in meconium staining, APGAR score at 5 minutes between the two groups (p=0.881, 0.884 respectively). Conclusions: Caesarean section for fetal distress and low birth weight babies was significantly associated with low amniotic fluid index. There was no significant difference in meconium staining liquor, APGAR score at 5 minutes between the two groups.